Arts of India : From Prehistoric to Modern Times. - Ajit (Tuttle Publishing, 1966)
This revised and enlarged edition of The Arts of India has over 150 impressive gravure and full-color illustrations. These include various important objects and monuments not usually seen in general surveys to supplement the many essential art milestones that this book features. It is also unique in beginning its visual survey with relics of India's stone age and in concluding the book with works from the nation's great folk tradition and selected paintings by modern artists. Here is a book with captions and a text that are highly readable blends of scholarly information and informal comment by.